The Design of Modular Oil Tank: A New Design Process Model - Li, Jin; Jiang, Xingsheng; Li, Jingye; Zhao, Yadong; Li, Xuexing (Recent Patents on Engineering, 2022)
Background: In the whole design process of modular fuel tank, there are some unreasonable phenomena. As a result, there are some defects in the design of modular fuel tank, and the function does not meet the requirements in advance. This paper studies this problem. Objective: Through on-the-spot investigation of the factory, a mechanical design process model is designed. The model can provide reference for product design participants on product design time and design quality, and can effectively solve the problem of low product design quality caused by unreasonable product design time arrangement. Methods: After sorting out the data from the factory investigation, computer software is used to program and simulate the information input of mechanical design process, and the final reference value is obtained. Results: This mechanical design process model is used to guide the design and production of a new project, nearly 3 months ahead of the original project completion time. Conclusion: This mechanical design process model can effectively guide the product design process, which is of great significance to the whole mechanical design field.
Keywords: ergonomics